Effect of Trichoderma and hydrogel on growth, yield and yield attributes of direct seeded rice (Oryza sativa) under rainfed condition - SEN, AVIJIT; SINGH, RAM KUMAR; YADAW, DESHRAJ; KUMARI, PUJA; SRIVASTAVA, V K; UPADHYAY, PRAVIN KUMAR; SANKAR, ARDITH; MISHRA, JYOTIPRAKSH; DAS, AJOY; ZAIDI, NAJAM WARIS; DAR, MANZOOR HUSSAIN (The Indian Journal of Agricultural Sciences, 2019)
A trial was conducted both in field and pot during the kharif season of 2015 at Banaras Hindu University, India to study the effect of hydrogel in combination with bio-agent on the performance of rice under rainfed condition. The field trial consisting of IR64 and DRR42 and Trichoderma and hydrogel making 10 treatments altogether was laid out in a Randomized Complete Block Design (RCBD) while in case of pot it was a factorial experiment. DRR42 + hydrogel (seed coating)+Trichoderma (seed treatment @ 12 g/kg) recorded higher yield (2.83 t ha-1) which was 43.76% higher than control but it remained at par with IR64. In the pot experiment hydrogel (seed coating)+Trichoderma (seed treatment) and hydrogel soil application registered higher RGR, CGR, root length, root weight. Survival of plants after imposition of drought at 60 days after sowing (DAS) was also found to be longer under the same treatments.